2018
DOI: 10.1007/s00018-017-2735-2
|View full text |Cite
|
Sign up to set email alerts
|

An MD2-derived peptide promotes LPS aggregation, facilitates its internalization in THP-1 cells, and inhibits LPS-induced pro-inflammatory responses

Abstract: MD2, a 160-residue accessory glycoprotein, is responsible for the recognition and binding of Gram-negative bacterial membrane component, lipopolysaccharide (LPS). Internalization of pathogen inside the mononuclear phagocytes has also been attributed to MD2 which leads to the clearance of pathogens from the host. However, not much is known about the segments in MD2 that are responsible for LPS interaction or internalization of pathogen inside the defense cells. A 16-residue stretch (MD54) from MD2 protein has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…The first signaling event of these pathways is NF-κB activation through TLR4 activation [24]. To investigate how the individual CD14, TLR4, and MD2 proteins contribute to the responses of cells to CL, we used the HEK transfection model where we can control which protein (including from different species) may be added to the cells and their contribution to CL activation of Nf-κB [21, 30, 31]. We transfected HEK293 cells with human or murine CD14 and MD2 with or without TLR4 and incubated them with saturated CLs for 6 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The first signaling event of these pathways is NF-κB activation through TLR4 activation [24]. To investigate how the individual CD14, TLR4, and MD2 proteins contribute to the responses of cells to CL, we used the HEK transfection model where we can control which protein (including from different species) may be added to the cells and their contribution to CL activation of Nf-κB [21, 30, 31]. We transfected HEK293 cells with human or murine CD14 and MD2 with or without TLR4 and incubated them with saturated CLs for 6 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that the MD2 and TLR4 signaling pathways play an important role in acute inflammation (23,24). Our previous research also identified a crucial role of these pathways in some chronic diseases, such as diabetes (25,26), obesity (27,28), etc.…”
Section: Discussionmentioning
confidence: 61%
“…MD2 has been well recognized as an indispensable accessory protein linking LPS and TLR4 [15,16], and targeting MD2 could effectively attenuate LPS-induced inflammatory response and sepsis [13,17,18]. Recently, we further prove that MD2 could also be an attractive therapeutic target for the treatment of many non-infectious chronic inflammatory diseases, including cardiac/kidney injuries induced by hypertension [19], obesity [20,21], and diabetes [22].…”
Section: Discussionmentioning
confidence: 89%